Perancangan Rangka Tandon Air Berkapasitas 1200 Liter Untuk Kebutuhan Pelaku Usaha Rumah Kost - Lukman, Muh Rahmat; Sudia, Budiman; Samhuddin, Samhuddin; Aminur, Aminur (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2024)
The increasing public interest in the need for adequate housing, especially the boarding house business, is one of the facilities that has great opportunities every year. The need for clean water in a boarding house environment is a factor that needs to be considered because clean water is an important need in human life. The water reservoir frame design with a capacity of 1200 liters is an optimized solution to meet the daily water needs of boarding house residents. The aim of this research is to design a water reservoir frame for water loads and carry out structural calculations of the water reservoir frame in accordance with applicable safety and strength standards. The research methodology explains in detail the research method which includes time and place of research, tools and materials, research procedures and research flow diagrams. Weight of load to be supported by the structure = weight of tank + weight of water Specify tank Type = Penguin TB, 120 uk Capacity = 1200 Liters = 1.2 m3 Tank mass (mT) = 29 kg Total mass of external load (mtot) = tank mass + water mass Mtot= 29 kg + 1200 kg = 1229 kg Total weight (Wtot) Wtot = (mtot) × g, g= acceleration due to gravity (9.8 m/s2) Kata kunci: Water discharge, Frame Strength, Structural Strength, Steel Selection, Water Reservoir